2019
DOI: 10.1126/science.aau8959
|View full text |Cite|
|
Sign up to set email alerts
|

Opposing reactions in coenzyme A metabolism sensitize Mycobacterium tuberculosis to enzyme inhibition

Abstract: Mycobacterium tuberculosis (Mtb) is the leading infectious cause of death. Synthesis of lipids critical for Mtb’s cell wall and virulence depends on phosphopantetheinyl transferase (PptT), an enzyme that transfers 4’-phosphopantetheine (Ppt) from coenzyme A to diverse acyl carrier proteins (ACPs). We identified a compound that kills Mtb by binding and partially inhibiting PptT. Killing of Mtb by the compound is potentiated by another enzyme encoded in the same operon, Ppt hydrolase (PptH), that undoes the PptT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
116
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(119 citation statements)
references
References 47 publications
(66 reference statements)
2
116
0
Order By: Relevance
“…Soluble, active protein was overexpressed by removing 20 amino acids from the C‐terminus while changing from BL‐21 DE3 to the BL‐21 AI strain further improved yields and mitigated the toxicity associated with the protein's expression without induction. This purified protein was used in the biochemical analysis that confirmed its activity as a Ppt hydrolase …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Soluble, active protein was overexpressed by removing 20 amino acids from the C‐terminus while changing from BL‐21 DE3 to the BL‐21 AI strain further improved yields and mitigated the toxicity associated with the protein's expression without induction. This purified protein was used in the biochemical analysis that confirmed its activity as a Ppt hydrolase …”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 colonies we identified that were resistant to the lead molecule 8918, 10 contained mutations within the rv2795c ( pptH ) gene. The fact that the same resistance phenotype was observed in the pptH deletion strains suggested that these mutations were LOF, and the presence of a WT pptH copy restored the sensitivity of resistant mutant Mtb cells to 8918 . However, without structural knowledge, the specific impact of these mutations on PptH was speculative.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations